Safety and long-term outcomes of remote cardiac rehabilitation in coronary heart disease patients: A systematic review - Antoniou, Varsamo; Kapreli, Eleni; Davos, Constantinos H; Batalik, Ladislav; Pepera, Garyfallia (Digital health, 2024)
OBJECTIVE: To systematically review the safety and the long-term mortality and morbidity risk-rates of the remotely-delivered cardiac rehabilitation (RDCR) interventions in coronary heart disease (CHD) patients. METHODS: The protocol was registered in the International Prospective Register of Systematic Reviews (CRD42023455471). Five databases (Pubmed, Scopus, Cochrane Central Register of Controlled Trials in the Cochrane Library, Cinahl and Web of Science) were reviewed from January 2012 up to August 2023. Inclusion criteria were: (a) randomized controlled trials, (b) RDCR implementation of at least 12 weeks duration, (c) assessment of safety, rates of serious adverse events (SAEs) and re-hospitalization incidences at endpoints more than 6 months. Three reviewers independently performed data extraction and assessed the risk of bias using the Cochrane Risk of Bias tool. RESULTS: 14 studies were identified involving 2012 participants and a range of RDCR duration between 3 months to 1 year. The incidence rate of exercise-related SAEs was estimated at 1 per 53,770 patient-hours of RDCR exercise. A non-statistically significant reduction in the re-hospitalization rates and the days lost due to hospitalization was noticed in the RDCR groups. There were no exercise-related deaths. The overall study quality was of low risk. CONCLUSIONS: RDCR can act as a safe alternative delivery mode of cardiac rehabilitation (CR). The low long-term rates of reported SAEs and re-hospitalization incidences of the RDCR could enhance the uptake rates of CR interventions. However, further investigation is needed in larger populations and longer assessment points.
Keywords: safety; systematic review; digital cardiac rehabilitation; remote; morbidity; mortality rate; digital health; Cardiac rehabilitation; coronary heart disease